PRISMA 2020 explanation and elaboration: updated guidance and exemplars for reporting systematic reviews. (29th March 2021) - Page, Matthew J; Moher, David; Bossuyt, Patrick M; Boutron, Isabelle; Hoffmann, Tammy C; Mulrow, Cynthia D; Shamseer, Larissa; Tetzlaff, Jennifer M; Akl, Elie A; Brennan, Sue E; Chou, Roger; Glanville, Julie; et al.
Abstract : The methods and results of systematic reviews should be reported in sufficient detail to allow users to assess the trustworthiness and applicability of the review findings. The Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement was developed to facilitate transparent and complete reporting of systematic reviews and has been updated (to PRISMA 2020) to reflect recent advances in systematic review methodology and terminology. Here, we present the explanation and elaboration paper for PRISMA 2020, where we explain why reporting of each item is recommended, present bullet points that detail the reporting recommendations, and present examples from published reviews. We hope that changes to the content and structure of PRISMA 2020 will facilitate uptake of the guideline and lead to more transparent, complete, and accurate reporting of systematic reviews.